STRATEGI PENGEMBANGAN DAYA TARIK WISATA BANGSRING UNDERWATER BERBASIS MASYARAKAT - Muhammad Ridla; Ka nom; Randhi Nanang Darmawan (STIE Pariwisata API Yogyakarta, 2021)
Bangsring Underwater is one of the natural tourism attractions in Banyuwangi. Located in Bangsring village, Wongsorejo subdistrict, Banyuwangi regency. Bangsring Underwater is known for its underwater natural beauty that continues to be maintained and developed by community. The aims of the study are: 1) to find out what are the supporting factors and inhibitory factors in the development of community-based Bangsring Underwater tourism attraction. 2) find out of strategy of developing community-based tourism. Data collecting are observations, in-depth interviews, and documentation. By using SWOT as data analysis tools in the form of (Strength, Weakness, Opportunities And Threats). The results of this study found the presence of several supporting factors such as; a) supported by the local government, b) the village government of Bangsring, c) the tourism conscious group Samudra Bhakti (pokdarwis Bangsring Underwater) in the development of the attraction of Bangsring Underwater. And factors several inhibitory factors such as; a) lack of human resources and b) some surrounding communities that have not been able to accept the existence of tourism activities in the tourist attraction Bangsring Underwater. In addition, this study also found seven alternative strategies obtained from SWOT analysis resulted in seven such strategies; (SO) tourism attraction development strategy, and tourism attraction promotion strategy. (WO) strategy improves safety and comfort. (ST) strategy to improve the quality of the environment, and sustainable tourism development strategy. (WT) human resource development strategy, and strategy to increase cooperation with elements of government and private partnerships.